Modeling And Control Of Lane Keeping System For Autonomous Vehicle - Ahmed, Sharmin (2016)
Control of autonomous ground vehicle has been one of the most vital topic of research in recent times. Among many features, lane keeping of ground vehicle has caught the attention of the researchers for its immense need in the passenger cars to avoid accidents and congestion. In this research a mathematical model of ground vehicle is developed from the lateral dynamics. The steering angle and the road curvature acts as the control input and the disturbance input of the vehicle respectively. Then with the help of conventional control method the vehicle is controlled to keep the lane. Later, model predictive control is applied for controlling the vehicle model. For both conventional and model predictive control approaches, the stability and robustness of the closed loop control system is conducted on dry and wet road condition. For robustness analysis, parametric uncertainty is added in the vehicle model, where road-tire friction coefficient and look ahead distance are assumed as uncertain parameters. Robustness of the proportional, integral, derivative control is not satisfactory in the presence of parametric uncertainty but the model predictive controller is robust enough in the presence of uncertain road-tire friction coefficient and look ahead distance.